2022
DOI: 10.3389/fsufs.2022.943237
|View full text |Cite
|
Sign up to set email alerts
|

Identifying wild bee visitors of major crops in North America with notes on potential threats from agricultural practices

Abstract: Considering the critical importance of insect pollination to food security and documented declines in wild bee populations, it is imperative to develop effective conservation and management strategies that promote the health of wild bee communities associated with agroecosystems. Identifying wild bee visitors of crops, including crop-flower visitors and species that nest within cropping areas, may prove critical to this endeavor as optimal conservation strategies may differ among bee species and/or guilds, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…If the goal is to safeguard wider pollinator biodiversity (species richness), more habitat and distinctly different habitat types are required (Fig. 4 ) than if the goal is to enhance crop pollination through increasing the abundance of specific functional groups or indeed particularly important species that dominate crop flower visitation 33 , 34 (Fig. 2 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…If the goal is to safeguard wider pollinator biodiversity (species richness), more habitat and distinctly different habitat types are required (Fig. 4 ) than if the goal is to enhance crop pollination through increasing the abundance of specific functional groups or indeed particularly important species that dominate crop flower visitation 33 , 34 (Fig. 2 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…An impressive number of specimens (>16,000) have been collected by community scientists during the project, permitting the identification of ≥252 species of bees (out of a total of 298 species recorded for Quebec; The Royal Saskatchewan Museum (2023)) and 86 species of hover flies (out of 413 species known in Eastern North America; Skevington et al (2019)). In comparison, a recent review of the bee fauna associated with agriculture in North America reported a total number of 185 bee species for the Province of Quebec from 11 monitoring studies conducted between 1967 and 2021 (Rondeau et al, 2022) while 200 species were reported for the cities of Montreal and Quebec (Normandin et al, 2017). For hover flies, previous studies have reported a total number of 28 species in lowbush blueberry (Moisan‐DeSerres et al, 2015), 33 species in cranberry crops (Gervais et al, 2018), and 48 species in urban green spaces (McCune et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…), several species of which have been shown to be declining in the province of Ontario and western Canada (Colla & Dumesh, 2010;Colla & Packer, 2008;Colla & Ratti, 2010;Macphail et al, 2019). In Quebec, short-term surveys have been conducted in agricultural (Gervais et al, 2017(Gervais et al, , 2018Moisan-Deserres et al, 2014;Moisan-DeSerres et al, 2015;Rondeau et al, 2022;Slupik et al, 2022) and urban (MacInnis et al, 2023;Martins et al, 2017;Normandin et al, 2017) areas, but more work is needed to reliably assess trajectories of wild bee communities over time and to forecast their resilience to ongoing and future perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These queens are the only individuals that survive the winter, while the workers and males perish before the winter months. While allowing the queens to escape the cold, underground overwintering means that diapausing queens are exposed to various stressors such as parasites [8,9], mould [10,11], soil contaminants [12][13][14] and flooding [15].…”
Section: Introductionmentioning
confidence: 99%